Estimation of Effective Pad Positions During Cardioversion Using 3-dimensional Finite Element Model - Chaugai, Varsha; Adler, Andy; Chan, Adrian D. C.; Zakutney, Timothy (CMBES Proceedings, 2012)
No Abstract